Nepāla (rtu-pau) yā cvasu-dhalaḥ = Bibliography of Nepal, bimonthly - Siṃha, Tulasī (Jñāna Bahādura Maharjana, 1978)
Bibliography of poems, essays, short stories, etc. published in Nepāla, a Newari bimonthly.